2016
DOI: 10.1007/s00204-016-1753-4
|View full text |Cite
|
Sign up to set email alerts
|

Hydroquinone-induced FOXP3-ADAM17-Lyn-Akt-p21 signaling axis promotes malignant progression of human leukemia U937 cells

Abstract: Hydroquinone (1,4-benzenediol; HQ), a major marrow metabolite of the leukemogen benzene, has been proven to evoke benzene-related hematological disorders and myelotoxicity in vitro and in vivo. The goal of the present study was to explore the role of FOXP3 in HQ-induced malignant progression of U937 human leukemia cells. U937 cells were treated with 5 μM HQ for 24 h, and the cells were re-suspended in serum-containing medium without HQ for 2 days. The same procedure was repeated three times, and the resulting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 56 publications
0
1
0
1
Order By: Relevance
“…• reduces BTRC mRNA stability in response to hydroquinone [155] and quinacrine [156] in U937 cells promoting [155] suppressive [156] [155,156] miR-193a-3p β-TrCP1…”
Section: Regulation Of β-Trcp Activity 61 Upstream Effectors Of β-Trc...mentioning
confidence: 99%
See 1 more Smart Citation
“…• reduces BTRC mRNA stability in response to hydroquinone [155] and quinacrine [156] in U937 cells promoting [155] suppressive [156] [155,156] miR-193a-3p β-TrCP1…”
Section: Regulation Of β-Trcp Activity 61 Upstream Effectors Of β-Trc...mentioning
confidence: 99%
“…Hydroquinone (HQ) induces the demethylation of the Forkhead box protein P3 (FOXP3) gene, resulting in FOXP3 gene expression in U937 cells [155]. As a result, FOXP3 induces the expression of miR-183, leading to a reduction in β-TrCP1 mRNA stability.…”
Section: Piceatannol Sykmentioning
confidence: 99%
“…Extensive research has shown that HQ may contribute to benzene-induced leukemia by oxidative stress, DNA damage, cell cycle regulation, and apoptosis [ 4 10 ]. HQ can inhibit erythroid differentiation in HD3 chicken erythroblast cells, K562 human leukemia cells, and U937 human leukemia cells [ 4 , 11 14 ]. Our previous studies suggest that benzene metabolite phenol, 1,2,4-benzenetriol, and HQ considerably inhibit hemin-induced erythroid differentiation in K562 cells [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…O maior tempo de exposição foi empregado com base na literatura em estudos de exposição à fumaça de cigarro para avaliação da toxicidade ao sistema imune e pulmonar, que variaram de 4 semanas ou mais de exposição (LIANG et al, 2018;SINZATO et al, 2018;VAZ et al, 2015;ZHOU et al, 2018) SNYDER, 2012;STABBERT et al, 2017). Considerando que a HQ é um dos principais produtos desta metabolização e estudos in vitro e in vivo mostram que a HQ inibe a proliferação de linfócitos, induz apoptose e causa genotoxicidade nas células da medula óssea, tem sido atribuído que a HQ seja o metabólito do BZ responsável pela toxicidade na medula (CHEN et al, 2017;LAU et al, 2009;MILLER et al, 1994;MORAN et al, 1996;RUIZ-RAMOS et al, 2017). Os dados aqui obtidos mostraram que a exposição à HQ reduziu a série eritrocítica, embora em pequena magnitude, após poucas semanas de exposição.…”
Section: Discussionunclassified